2022
DOI: 10.3389/ffgc.2022.903607
|View full text |Cite
|
Sign up to set email alerts
|

Life-stage dependent response of the epiphytic lichen Lobaria pulmonaria to climate

Abstract: Lichens are poikilohydric organisms, whose internal water content tends to reflect external humidity conditions. After drying, they can reactivate their metabolic activity through water vapor uptake or liquid water input. Thus, lichen water-related functional traits are important as they are involved in the duration of the hydrated period. Models predicting the effect of environmental conditions on lichens are based mainly on the presence or absence of adult thalli. Nevertheless, ecological conditions required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…This may provide a potential explanation for the modelling result that no or weak competitive exclusion best explains observed trait distributions. While facilitative interactions are not explicitly included in the model, some positive community‐level effects are represented by parameterized ecophysiological relations of the strategies, such as the decreasing effect of height on evaporation (Di Nuzzo et al., 2022), which only becomes effective when growing in a cushion. Several studies have found that facilitation arises frequently between associated lichens and bryophytes (Colesie et al., 2012), and when interacting species acquire resources in complementary ways (Bowker et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This may provide a potential explanation for the modelling result that no or weak competitive exclusion best explains observed trait distributions. While facilitative interactions are not explicitly included in the model, some positive community‐level effects are represented by parameterized ecophysiological relations of the strategies, such as the decreasing effect of height on evaporation (Di Nuzzo et al., 2022), which only becomes effective when growing in a cushion. Several studies have found that facilitation arises frequently between associated lichens and bryophytes (Colesie et al., 2012), and when interacting species acquire resources in complementary ways (Bowker et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…and Nikolić et al (2024) present methodologies for predicting climate change impacts on lichens, offering a framework for future research in "Burabay" and beyond. Ås Hovind et al (2020) and DiNuzzo et al (2022) explored lifestage dependent responses to climate, which could inform management strategies for preserving lichen diversity in changing climates. Studies byMunzi et al (2019) andYang et al (2023) on the physiological responses of lichens to drying periods provide a mechanistic understanding of how aridification affects lichen biology, complementing our observations of community-level changes.…”
mentioning
confidence: 99%